Generating a magellanic star cluster catalog with ASteCA - Perren, Gabriel Ignacio (2016)
An increasing number of software tools have been employed in the recent years for the automated or semi-automated processing of astronomical data. The main advantages of using these tools over a standard by-eye analysis include: speed (particularly for large databases), homogeneity, reproducibility, and precision. At the same time, they enable a statistically correct study of the uncertainties associated with the analysis, in contrast with manually set errors, or the still wide spread practice of simply not assigning errors. We present a catalog comprising 210 star clusters located in the Large and Small Magellanic Clouds, observed with Washington CT 1 photometry. Their fundamental parameters were estimated through an homogeneous,automatized and completely unassisted process, via the Automated Stellar Cluster Analysis package (ASteCA).Our results are compared with two types of studies on these clusters: one where the photometry is the same, andanother where the photometric system is different than that employed by ASteCA.